Medium entropy alloys for biomedical applications - Zhang, Jiacheng; Stiehler, Martin E.; Syed, Adnan U.; Jorge Jr, Alberto Moreira; Jolly, Mark R.; Georgarakis, Konstantinos (Cranfield University, 2024)
High entropy alloys (HEAs) is a rapidly emerging class of metallic materials consisting of four or more elements in equimolar or quasi-equimolar compositions. These alloys often have simple crystal structures and tailorable properties attracting significant interest for different applications. Common metallic materials for orthopaedic and dental implants include stainless steel, Co-Cr and Ti- alloys. Although these materials are widely in use, issues relevant to biocompatibility and suspected toxicity and the elastic modulus mismatch compared to that of hard tissue have been raised in recent years. High entropy alloys specifically designed for bio-medical applications can offer solutions to overcome these limitations. Bio-HEAs have emerged in the last couple of years and currently receive increasing scientific attention. In this work, we discuss on the design of new entropic alloys using only non-toxic elements such as Ti, Zr, Nb, Ta and Mo. We use a systematic approach to investigate the effect of additional elements on the microstructure and properties of the alloys starting from the binary Ti-Nb and extending to the ternary Ti-Zr-Nb, the quaternary Ti-Zr-Nb-Ta and the Ti-Zr-Nb-Ta-Mo alloy. The alloy design is building on previous work on beta Ti- alloys which has shown promising trends for reducing the elastic modulus of implant materials. The alloys were produced by arc-melting and suction casting under Ar inert atmosphere. X-ray diffraction, and scanning electron microscopy were employed to reveal their crystal structure and microstructure. respectively. The developed alloys exhibit BCC crystal structure and a dendritic microstructure in their as-cast condition. The addition of Zr and Mo was found to increase the hardness of the alloys.
Winner of Best Paper Award.
Keywords: Biomedical materials; High / medium entropy alloys; multi principal element alloys; β-phase Ti alloy; Ti-based alloys.